Land Reform and Development Strategy in Zimbabwe: State Autonomy, Class and Agrarian Lobby - Moyo, Sam; Skalness, Tor (Afrika Focus, 1990)
Much of the literature on the political determinants of African economic policies that has been produced over the last decade seems to be motivated by the need to make some sense out of the following apparent fact. Even as the characteristic policies pursued by African governments have been shown to have severely adverse consequences, sufficient internal forces are seldom mobilised to have them substituted for a more ’realistic’ set of policies. Sustained external pressure from the International Monetary Fund, the World Bank and other international donors seems to be necessary for such policy reorientation to occur. In other words, writers searching for the political rationality behind the typical set of African economic policies seem to assume that these policies are economically ’irrational’. If that assumption is accepted as valid, explanations of policy outcomes in terms of the dominance over the policy process of a certain coalition of special interests (for instance, Bates, 1981) attain inherent plausibility. This is so because we tend to believe that in the absence of strong political pressure to the contrary, governments would choose policies that promote growth, a sustainable balance of payments, and generally increased economic well-being for the country as a whole. It is not our intention to challenge the assumption of the economic destructiveness of past African policies here. Rather we shall concern ourselves with an issue on which there is very little consensus as to what policy direction would produce the greatest net benefit to the country as a whole, i.e., what would consitute the economically sensible course of action for a given country to pursue. This issue is land reform, and the empirical case is Zimbabwe. Since no particular course of action can simply be assumed to be economically rational as far as land reform is concerned, the task of the political scientist becomes more difficult. Simply assuming that a given decision comes about as the result of political pressure by the beneficiaries of that policy will not do. As we shall see below, proponents of land reform have been hard pressed first to show that there is indeed an economic case to be made for transformation in the ownership structure of land in Zimbabwe. Only then can the fact that no truly radical land reform has occurred in Zimbabwe plausibly be explained in terms of a particular ’disadvantageous’ constellation of group and/or class forces. However, because the economic arguments against land reform have by no means been fully rebutted, there exists another possible explanation, viz. that the Zimbabwean state acts cautiously on the issue simply because it perceives radical land reform to be too risky in national economic terms. The unresolved nature of the question of the economic consequences of land reform thus forces us (1) to carefully consider the arguments made for and against structural changes, as well as (2) to consider explanations in terms of autonomous class action as well as hypotheses derived from group or class theory.